2007
DOI: 10.1007/s10522-007-9108-4
|View full text |Cite
|
Sign up to set email alerts
|

The senescence-accelerated mouse (SAM-P8) as a model for the study of vascular functional alterations during aging

Abstract: We studied vascular function in quiescent aortas from senescence-accelerated resistant (SAM-R1) and prone (SAM-P8) mice. Myographical studies of thoracic aorta segments from 6-7 month-old mice showed that the contractility of SAM-P8 aortas was markedly higher than that of SAM-R1 after KCl depolarization or phenylephrine addition. Acetylcholine dose-response relaxation curves revealed that SAM-R1 vessels were slightly more sensitive than those of SAM-P8. In the presence of the NO synthase inhibitor, L-NAME, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Moreover, the absence of vascular damage at early age (Butterfield and Poon, 2005) establishes SAM as an optimal model to study vascular aging. Functional studies on vascular function system and the role of NO, the key component of cardiovascular regulation, have been recently performed in male SAM (Llorens et al, 2007). Our studies provide, for first time, a description of changes in vascular reactivity in female, using SAM as a model of aging.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the absence of vascular damage at early age (Butterfield and Poon, 2005) establishes SAM as an optimal model to study vascular aging. Functional studies on vascular function system and the role of NO, the key component of cardiovascular regulation, have been recently performed in male SAM (Llorens et al, 2007). Our studies provide, for first time, a description of changes in vascular reactivity in female, using SAM as a model of aging.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
“…SAM is a murine model that has been increasingly used to study aging-associated diseases, as it ages fast and predictably, allowing experimental work to be performed in a convenient and standard time course (Llorens et al, 2007). Moreover, the absence of vascular damage at early age (Butterfield and Poon, 2005) establishes SAM as an optimal model to study vascular aging.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The P8 substrain (SAM-P8) of these mice has a markedly shortened life span when compared to the R1 substrain (SAM-R1), which also shows a slower aging process [12]. In parallel with their premature aging, SAM-P8 mice also exhibit increased neurological senescence, immunosenescence, and age-related hematopoietic deficits which closely mimic typical human aging characteristics [13, 14]. Analysis of the underlying mechanisms responsible for the accelerated aging process and age-related disorders indicates that mitochondrial dysfunction [15], oxidative stress, and increased somatic DNA mutation rate all appear to be involved [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…These mice manifest several phenotypes including deficits in learning and memory, emotional disorders, abnormal circadian rhythms and impaired immune response (Takeda 1999). Different studies have suggested that SAM-P8 mice are a suitable model for the study of cardiovascular aging (Kurokawa et al 1998;Lloréns et al 2007). Mechanical and morphological alterations as well as endothelial dysfunction with loss in distensibility of the aorta, intima and medial thickening together with and increase in collagen accumulation in the media, and elastin fragmentation with a decline in endothelium-dependent relaxation has been observed in these mice (Lloréns et al 2007).…”
Section: Introductionmentioning
confidence: 99%